2017
DOI: 10.1177/0015732516663316
|View full text |Cite
|
Sign up to set email alerts
|

Zimbabwe’s Trade Performance Under Alternative Trade Policy Regimes

Abstract: This study examines Zimbabwe’s export and import performance under alternative trade policy regimes, from 1976 to 2014. Taking into account export and import volumes, gross domestic product (GDP), price of exports and imports, foreign income, real effective exchange rate and policy changes, log-linear errorcorrection models were adopted to estimate export supply and import demand elasticities. The study concludes that the relationship of exports and imports to GDP is significantly positive, while foreign incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
2
0
2
Order By: Relevance
“…Ceteris paribus, given a 1% increase in GDP, imports increase by 0.049% in the short run and 0.132% in the long-term. This result is consistent with previous studies by Warner and Kreinin (1983), Aydin et al (2004), Aziz (2013), Nyatanga (2017), amongst others, who found that an increase in a country's real income level leads to increased export and import volumes.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Ceteris paribus, given a 1% increase in GDP, imports increase by 0.049% in the short run and 0.132% in the long-term. This result is consistent with previous studies by Warner and Kreinin (1983), Aydin et al (2004), Aziz (2013), Nyatanga (2017), amongst others, who found that an increase in a country's real income level leads to increased export and import volumes.…”
Section: Resultssupporting
confidence: 93%
“…Relative price of exports = Export price index/ domestic prices Positive effect on export supply (Khan, 1974;Warner and Kreinin, 1983;Aziz, 2013;Nyatanga, 2017).…”
Section: Rpxmentioning
confidence: 99%
“…Model ECM pertama kali diperkenalkan oleh Sargan dan kemudian dikembangkan oleh Hendry dan juga Engle-Granger (Granger & Newbold, 1974). Model ECM memiliki beberapa kegunaan dalam mengatasi masalah data time series yang tidak stasioner dan masalah regresi lancung (spurious) (Nyatanga, 2017).…”
Section: Metode Ecmunclassified
“…Pendekatan ini muncul sejak para ahli ekonometrika memba masalah time series. Model ECM pertama kali diperkenalkan ole dikembangkan oleh Hendry dan juga Engle-Granger (Granger & ECM memiliki beberapa kegunaan dalam mengatasi masalah dat stasioner dan masalah regresi lancung (spurious) (Nyatanga, 2017).…”
Section: Uji Akar-akar Unitunclassified
“…This has resulted in the rapid growth in the services sector of the region, particularly in India where the contribution of services to overall growth has been significant and which has attracted substantial foreign direct investment (FDI) into the sector (IBEF, 2017). Despite the structural changes in South Asian economies over the past decade, the region has remained inward-looking (Nyatanga, 2017). In particular, trade among South Asian countries has remained much below potential, partly because of tariff and non-tariff barriers (Kaur & Nanda, 2010).…”
Section: Introductionmentioning
confidence: 99%